An efficient quantum blind digital signature scheme - Lai, Hong; Luo, Mingxing; Pieprzyk, Josef; Qu, Zhiguo; Li, Shudong; Orgun, Mehmet A. (Science China. Information sciences, 2017)
Recently, many quantum digital signature（QDS） schemes have been proposed to authenticate the integration of a message. However, these quantum signature schemes just consider the situation for bit messages,and the signing-verifying of one-bit modality. So, their signature efficiency is very low. In this paper, we propose a scheme based on an application of Fibonacci-, Lucas-and Fibonacci-Lucas matrix coding to quantum digital signatures based on a recently proposed quantum key distribution（QKD） system. Our scheme can sign a large number of digital messages every time. Moreover, these special matrices provide a method to verify the integration of information received by the participants, to authenticate the identity of the participants, and to improve the efficiency for signing-verifying. Therefore, our signature scheme is more practical than the existing schemes.